P-187 Assistant practitioner – band 4 (AFC). one solution to improve retention and recruitment of clinical staff with the required skills. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Vandeweghe, Maaike; Wilcocks, Tricia; Berg, Jane; Bryan, Liz; Morris, Kathy; Linehan, Gail; Menezes, Toni; King, Helen; Forrest, Letizia Perna-; Moback, Berit; Jackson, Timothy; Betts, Caroline; et al.
Abstract : Background: The National End of Life Care Strategy (DoH) highlighted in 2008 the need to develop the workforce, including the non-registered workforce. Health Care providers also report challenges around the recruitment of Registered Nurses. The lack of career development for Health Care Assistants (HCAs) equally comes withits challenges going forward. The South London Hospice Education Collaborative (SLHEC) decided to work with Croydon College to develop a programme to deliver the City and Guilds Level 5 Diploma for Assistant Practitioners in healthcare. This a vocational higher apprenticeship programme for HCAs to prepare them for a Band 4 (Afc) post. The programme is delivered by hospice clinicians and Croydon College and funded by Health Education South London and the Skills Funding Agency. Aims: Deliver a bespoke educational programme Evaluate the educational programme and its impact on patient care Offer higher apprenticeship education Collaboration between eight hospice, one care home and Croydon College Delivery: Employers selected learners for this course through a process of application, interview and literacy/numeracy tests. The course started in March 2015 with 20 learners from adult and children's Hospices and one Care Home. Challenges: Ensuring that Band 4 (Afc) fits in with future workforce development/strategy at the individual Hospices and Care Home. Supporting learners, assessors and teachers across a number of organisations. Delivery of vocational programme by hospice staff in further education. Evaluation: Two Units completed and well evaluated by learners. The impact on patient care and workforce development will be evaluated as part of a Master's degree. Plans: Ensure sustainability Share learning with hospices and stakeholders Approach professional bodies/stakeholders to share to discuss recognition and registration of Assistant Practitioners